Strengthening rural development institutions (hemispheric) - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The results of this study are summarized in two conceptual papers presented in January 1990 at a consultative meeting of international experts, held to validate their contents. It covers harmonization of macroeconomic and sectoral and rural development policies, basic criteria for formulating differentiated policies, specific requirements of differentiated policies, modernization of institutions, decentralization of the state apparatus, strengthening of municipal governments, increased participation in state activities at the local level and training for civilian organizations in order to ensure decentralization and participation. The documents are entitled: Políticas diferenciadas para el desarrollo: enfoque conceptual y propuesta, and Descentralización y participación en la administración de políticas y programas de desarrollo rural. This process gave rise to the incorporation of a multinational project directly related to this topic, entitled strengthening rural development institutions into the PLANLAC. The purpose of the project is to support countries in formulating differentiated policies for rural development and in designing management models for formulating and executing such policies using decentralized and participatory techniques.